Empowering Female-Headed Households through Creative Waste Management: Transforming Textile Scraps into Cultural Mascot Dolls - Syarif, Ahmad; Aufa, Mohamad Nor; Purtina, Arna; Hasanah, Muqor Rama; Ramadhani, Riski Candra; Yutiva, Melan; Banjir, Banjir (Universitas Lambung Mangkurat, 2025)
This community service program aimed to empower female heads of households in the Bunda Sehati Community of Palangka Raya by enhancing their vocational skills and promoting sustainable waste management through the creative reuse of textile scraps. The service was implemented using a participatory community empowerment approach, emphasizing active engagement in each phase, including planning, implementation, and evaluation. Activities included technical training in sewing and crafting mascot dolls inspired by Central Kalimantan culture, financial literacy sessions, and digital marketing workshops. A Joint Business Group (Kelompok Usaha Bersama/KUB) was formed to sustain production and marketing efforts beyond the program. The evaluation combined quantitative and qualitative methods through pre- and post-program questionnaires, observations, focus group discussions, and income tracking. The results showed significant improvements in participants’ technical skills and entrepreneurial knowledge. Over 90% of participants completed all training modules, and more than 30% reported an increase in household income from product sales. Additionally, participants demonstrated greater awareness of the environmental impact of textile waste. The establishment of a functioning KUB enabled collaboration and continuity of the initiative. The program proved effective in achieving its goals by empowering economically vulnerable women, fostering sustainable micro-business development, and encouraging environmentally responsible practices. This model of community engagement can be adapted and scaled in other regions facing similar socio-economic and environmental challenges.